Relationship between Oxidative Stress and Cellular Adenosine Triphosphate Levels - Seval Bulut; Halis Süleyman (Atatürk University, 2024)
Oxidative stress (OS) refers to the deterioration of the balance between oxidants and antioxidants in favor of oxidants, and this may lead to disruptions in redox signaling and control and/or damage at the molecular level. The presence of low levels of reactive oxygen species (ROS) plays a physiological role in intracellular signaling pathways. However, damage may occur in cells and tissues as a result of excessive increase in ROS production. Because ROS have the potential to damage almost all structures in the cell, including lipid, protein, deoxyribo nucleicacid (DNA). The main source of free radicals in the cell is mitochondria. ROS formation is a natural consequence of oxidative phosphorylation resulting in adenosine triphosphate (ATP) production in mitochondria. The attack of these radicals results in damage to the mitochondria, a decrease in the activity of oxidative phosphorylation enzymes and consequently a decrease in ATP synthesis. On the other hand, ATP is needed for antioxidant synthesis, which is necessary for cell defence against increasing ROS. Therefore, a decrease in ATP levels makes tissues vulnerable to OS. In this case, it is likely that tissues exposed to OS will also have problems in ATP production and the decrease in ATP synthesis will further increase oxidative damage.